Information needed to facilitate the clarity, transparency and understanding of mitigation contributions - Moarif, Sara (OECD Publishing, 2017)
Parties to the United Nations Framework Convention on Climate Change are currently developing the operational elements of the Paris Agreement, including guidance for information to facilitate clarity, transparency and understanding (CTU) when Parties communicate their nationally determined contributions (NDCs). Drawing on Party submissions from 2016 and April 2017, and discussions held during the CCXG Global Forum on the Environment and Climate Change in March 2017, this paper synthesises and discusses views on guidance for CTU in four areas: the purpose of the guidance; where further guidance is needed; the elements of the guidance; and the relationship between guidance for CTU and other operational elements of the Paris Agreement. The paper then suggests ways for Parties to consider selected issues, namely: the structure and content of the guidance; its status; the scope of NDCs; and links between sets of guidance, including timing issues
Keywords: Environment